Cephalometric and dental casts comparison of cases treated with Damon self-ligating or conventional fixed appliances with and without rapid maxillary expansion - Furquim, Bruna Alves (2015)
Purpose: To compare the changes in the maxillary and mandibular dental arch forms and in incisors position in orthodontic cases treated with Damon and conventional appliances, with and without rapid maxillary expansion (RME). Methods: Sample comprised 75 Class I malocclusion patients with mild to moderate crowding treated orthodontically without extractions. The sample was divided into 3 groups: Group 1: 23 patients (mean initial age: 14.65 years) treated with Damon System for a mean period of 2.72 years; Group 2: 24 patients (mean initial age: 13.85 years) treated with RME followed by conventional fixed appliances for a mean period of 2.17 years; Group 3: 28 patients (mean initial age: 13.94 years) treated with conventional fixed appliances for a mean period of 2.20 years. Pretreatment and posttreatment dental casts and cephalograms of each patient were evaluated. Intergroup comparison of the variables was performed by ANOVA and Tukey test. Results: The maxillary intercanine, inter-second-premolar and intermolar widths showed a greater increase in Damon and RME groups. In the mandibular arch, the arch widths showed a greater increase in Damon group compared to the other two groups. There was greater protrusion of the maxillary incisors in Damon group than in the other 2 groups. For the mandibular incisors, Damon caused a greater protrusion and proclination when compared to the conventional appliance. Conclusions: The maxillary arch form showed similar increases in most of the distances to treatment with Damon and RME plus conventional appliances. The mandibular arch showed a greater increase in most of the measured distances in cases treated with Damon, compared to the conventional appliances with and without RME. Damon caused greater protrusion of the maxillary incisors. In the mandibular incisors, Damon caused a greater protrusion and proclination when compared to conventional appliance only.